Protein Kinase Cδ and Calmodulin Regulate Epidermal Growth Factor Receptor Recycling from Early Endosomes through Arp2/3 Complex and Cortactin - Lladó, Anna (The American Society for Cell Biology, 2008)
The intracellular trafficking of the epidermal growth factor receptor (EGFR) is regulated by a cross-talk between calmodulin (CaM) and protein kinase Cδ (PKCδ). On inhibition of CaM, PKCδ promotes the formation of enlarged early endosomes and blocks EGFR recycling and degradation. Here, we show that PKCδ impairs EGFR trafficking due to the formation of an F-actin coat surrounding early endosomes. The PKCδ-induced polymerization of actin is orchestrated by the Arp2/3 complex and requires the interaction of cortactin with PKCδ. Accordingly, inhibition of actin polymerization by using cytochalasin D or by overexpression of active cofilin, restored the normal morphology of the organelle and the recycling of EGFR. Similar results were obtained after down-regulation of cortactin and the sequestration of the Arp2/3 complex. Furthermore we demonstrate an interaction of cortactin with CaM and PKCδ, the latter being dependent on CaM inhibition. In summary, this study provides the first evidence that CaM and PKCδ organize actin dynamics in the early endosomal compartment, thereby regulating the intracellular trafficking of EGFR.